Traumatic Brain Injury and Gut Brain Axis: The Disruption of an Alliance - Ferrara, Michela; Bertozzi, Giuseppe; Zanza, Christian; Longhitano, Yaroslava; Piccolella, Fabio; Lauritano, Cristiano E.; Volonnino, Gianpietro; Manetti, Alice Chiara; Maiese, Aniello; La Russa, Raffaele (Reviews on Recent Clinical Trials, 2022)
Background: Traumatic brain injury (TBI) can be considered a
Keywords: Traumatic brain injury